2020
DOI: 10.1787/9988df4e-en
|View full text |Cite
|
Sign up to set email alerts
|

A tool to capture learning experiences during Covid-19

Abstract: Unclassified OECD EDUCATION WORKING PAPERS SERIES OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed herein are those of the author(s). Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcome, and may be sent to the Directorate for Educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…At the same time, they all encounter numerous technical problems. Similar experiences were noted in other research that included students and teachers during the Covid-19 crisis: losses in wellbeing, feeling of belonging, and confidence in their competences (Bertling et al, 2020;Niemi & Kousa, 2020;Trust & Whallen, 2020).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…At the same time, they all encounter numerous technical problems. Similar experiences were noted in other research that included students and teachers during the Covid-19 crisis: losses in wellbeing, feeling of belonging, and confidence in their competences (Bertling et al, 2020;Niemi & Kousa, 2020;Trust & Whallen, 2020).…”
Section: Discussionsupporting
confidence: 81%
“…The year 2020 was exceptional for education systems globally. The Covid-19 pandemic led to unprecedented disruptions in schooling around the world (Bertling et al, 2020), which exacerbated already known education policy fractures and put the quality, equity and effectiveness of education at risk (Schleicher, 2020). It forced school closures, the introduction of emergency distance education, and experimentation with various hybrid and blended educational models, thus leaving more than 1.5 billion children temporarily out of school (UNESCO, 2020a) and exposing all education participants to an incommensurable degree of uncertainty and ambiguity (Bergdahl & Nouri, 2020;Gudmundsdottir & Hathaway, 2020;Hodges et al, 2020;Trust & Whalen, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently there is a lack of research involving secondary and high-school students, especially with assessment of students' skills and abilities. OECD has published an extensive survey tool for a comprehensive assessment of the distance learning situation "The PISA Global Crises Questionnaire Module" (Bertling et al, 2020), based on which we could eventually gain comparable data from many countries of the world. The limitation with some of the currently available research is that they do not show the full picture of psychological constructs (e.g., depression, anxiety) and rarely measure students' skills and abilities; some conclusions are based on single question measurements.…”
Section: Research On Students' Skills and Attitudes During The Covid-19 Related Distance Learningmentioning
confidence: 99%
“…Prior research has demonstrated, however, that "disruption can be a powerful avenue for growth" (Gilbert, 2003, p. 27), at times giving birth to new forms of innovation. Emergency remote teaching during international conflicts, for example, has mitigated disparities in equity and access (Bertling et al, 2020). In Afghanistan, when schooling was interrupted by significant security threats, distance education was found to promote education for girls (Davies, 2011).…”
mentioning
confidence: 99%